Analisis Tingkat Kepuasan Siswa Terhadap Layanan Konseling Individu - Nurhayati, Afifah; Hadi, Dzinnun (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2023)
This research aims to determine the level of student satisfaction with individual counseling services for classes X and XI at SMA Negeri 1 Tulungagung. The type of research used is quantitative research with a descriptive type. This research was carried out by analyzing data on the average percentage of student satisfaction. With a population of 118 and the research sample used total sampling or the entire population was used as a sample. The method for collecting data in this research uses a questionnaire. The results of the descriptive percentage analysis showed that the average satisfaction of class With a percentage of each aspect, namely the physical evidence aspect with a percentage of 21.89%, the reliability aspect with a percentage of 21.03%, the timeliness aspect with a percentage of 13.28%, the guarantee aspect with a percentage of 13.45%, and the empathy aspect with a percentage of 17. .84%. The conclusion from this research is that the percentage of average student satisfaction is 7.14%, where the categorization is very dissatisfied.